2019
DOI: 10.1371/journal.pone.0210351
|View full text |Cite
|
Sign up to set email alerts
|

A proteome-wide screen of Campylobacter jejuni using protein microarrays identifies novel and conformational antigens

Abstract: Campylobacter jejuni (C. jejuni) is a foodborne intestinal pathogen and major cause of gastroenteritis worldwide. C. jejuni proteins that are immunogenic have been sought for their potential use in the development of biomarkers, diagnostic assays, or subunit vaccines for humans or livestock. To identify new immunogenic C. jejuni proteins, we used a native protein microarray approach. A protein chip, with over 1400 individually purified GST-tagged C. jejuni proteins, representing over 86% of the proteome, was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…A few conformation-dependent epitopes have also been described in bacterial proteins, such as E. ch. TRP32, Yersinia pseudotuberculosis OmpF porin, and Campylobacter jejuni membrane protein Cj1621 6,42,46 . These proteins have been demonstrated to play an important role in pathogen infection and eliciting host antibody response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few conformation-dependent epitopes have also been described in bacterial proteins, such as E. ch. TRP32, Yersinia pseudotuberculosis OmpF porin, and Campylobacter jejuni membrane protein Cj1621 6,42,46 . These proteins have been demonstrated to play an important role in pathogen infection and eliciting host antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent studies have revealed the functional aspects of TRPs, and it is now established that they are secreted effectors that interact with an array of host proteins and have various distinct functions during infection 38 41 . Hypothetical proteins have also been shown to be predominant immunoreactive proteins in other intracellular pathogens, suggesting that many antigenic and potentially protective proteins have unknown function 24 , 42 . Therefore, based on previous empirical data we considered hypothetical proteins to be higher priority candidates and the focus of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Six of them were tested on broilers in experimental husbandries and four candidates showed Campylobacter load decreases in caeca by 2-4 logs CFU/g correlated with the induction of specific humoral responses (Meunier et al, 2017). Liu et al (2019) used a native protein microarray approach and identified 30 new immunogenic C. jejuni proteins but no information was provided about in vivo testing. Vandeputte et al (2019) reported that in ovo-vaccinated birds using vaccines based on maternal antibodies were not protected with the treated birds showing similar caecal C. Jejuni concentrations to the control birds.…”
Section: Vaccinationmentioning
confidence: 99%
“…Liu et al. () used a native protein microarray approach and identified 30 new immunogenic C. jejuni proteins but no information was provided about in vivo testing. Vandeputte et al.…”
Section: Assessmentmentioning
confidence: 99%
“…Passive immunization could lower the possibility of colonization and transmission of C. jejuni in broiler chickens ( Hermans et al, 2014 ). So far, there has been no vaccine approved by any global regulatory authority targeted at preventing Campylobacter-associated diseases ( Liu et al, 2019 ). Nevertheless, several efforts are underway to design vaccines against C. jejuni , including the conventional approach of adopting the live attenuated or heat-killed whole cells as potential vaccines.…”
Section: Introductionmentioning
confidence: 99%